Cytotoxicity test and characteristics of demineralized dentin matrix scaffolds in adipose-derived mesenchymal stem cells of rats - Desi Sandra Sari; Ernie Maduratna; F. Ferdiansyah; I Ketut Sudiana; Fedik Abdul Rantam (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Demineralized dentin matrix (DDM) scaffold is a substitute material for the bone contained in human teeth. DDM is a scaffold-derived tooth dentine containing type I collagen and bone morphogenetic protein (BMP). While DDM possesses the ability to perform osteoinductive and osteoconductive roles, a cytotoxicity test of DDM scaffold remains extremely important in evaluating the level of toxicity of a material if cultured in cells. Adipose-derived mesenchymal stem cells (ADMSCs) are multipotent in nature because they contain progenitor cells and have the potential for differentiation via adipogenic, osteogenic and chondrogenic pathways. ADMSCs are also known to have high biocompatibility and the ability to combine with other bone material. Purpose: The purpose of this study was to determine the cytotoxicity and characteristics of DDM scaffolds derived from bovine teeth in the ADMSCs of rats cultured in vitro. Methods: This research constituted an experimental study. ADMSCs were isolated from the inguinal fat of rats. Thereafter, DDM was extracted from bovine teeth and formed 355-710 μm-sized particles. DDM scaffolds were assessed using SEM and the effects of DDM scaffolds on the cell viability of ADMSCs at concentrations of 10%, 50%, and 100% analyzed by means of 3-4,5’dimethylihiazol-2-yl,2.5-di-phenyl-tetrazolium bromide (MTT) assay. The results obtained were then analyzed by an ANOVA to establish the difference between the groups. Results: SEM results showed the diameter sizes of the dental tubulis DDM scaffolds to be approximately 4.429 μm and 7.519 μm. The highest cell viability (97.08%) was found by means of an MTT test to be in ADMSCs at a concentration of 10% compared to those at concentrations of 50% and 100%. Conclusion: In conclusion, DDM scaffold derived from bovine teeth with a particle size of 355-710 μm produces a low cytotoxicity effect on ADMSCs.